Saccharomyces cerevisiae Immobilisation in Sodium Alginate for Red Dragon Fruit Winemaking - N. P. Minh (Journal of Global Pharma Technology, 2019)
Red dragon fruit is rich in sugar, organic acids and minerals and other nutrients. It has good processing properties; it is used in the production of fruit juice, jam, and preserved fruit. Its economic value in local market is quite low. Making wine is not only converting the fruit into wine, but also improves its economic value of dragon fruit. Objective of this study focused on the effect of encapsulation of Saccharomyces cerevisiae in sodium alginate complexed with calcium chloride in red dragon fruit wine fermentation. Different technical parameters such as sodium alginate concentration (2.0%, 4.0%, 6.0%, 8.0%, 10%), bead size (2mm, 4mm, 6mm, 8mm, 10mm), bead loading (5 g/100ml, 10 g/ 100ml, 15 g/100ml, 20 g/ 100ml, 25 g/ 100ml), initial total soluble solid (10, 12, 14, 16, 18oBrix), clarifying agent (gelatin, bentonite, wheat gluten, egg white, kieselsol and kaolin) in wine making. Results showed that the best wine quality based on ethanol content (19.38%v/v) and sensory score were recorded by encapsulation of Saccharomyces cerevisiae in 6% sodium alginate, bead size 6mm, bead loading 20 g/ 100ml, initial soluble solid 16%, gelatin as clarifying agent.Keywords: Dragon fruit, Sodium alginate, Calcium chloride, Saccharomyces cerevisiae, Encapsulation, gelatin, Wine.